Rural student experience of spatial inequality in higher education : a case study in Kumi, Uganda - Yang, Sion (2023)
One of the prominent factors of intranational inequalities that are prevailed globally is the urban-rural disparity in living standards. This disparity leads to unequal access to educational opportunities and resources across geographical locations, creating spatial inequalities at various levels of education. Evidence suggests that the rural population in lower-income countries tends to be most vulnerable to inequalities in access to higher education (HE). Therefore, this study aimed to investigate spatial inequalities in HE in a developing, low-income country context through a qualitative case study of student experiences in a rural higher education institution (HEI) in Kumi District of Eastern Uganda. The findings from a thematic analysis of seven semi-structured focus group interviews suggested heavy dependency on agriculture for financing HE, the importance of accessibility and cultural belongingness in choosing an HEI, and the lack of educational resources as shared experiences among the rural students. Furthermore, the findings revealed rural student conceptualisations of disparities in living standards, infrastructure, and employability between urban and rural HEIs in Uganda. The study also shed light on the obstacles faced by refugees seeking to access HE from Uganda's conflict-affected neighbouring countries, South Sudan and the Democratic Republic of the Congo. Despite the revealed challenges of ensuring access to quality HE in rural Uganda, HE in a rural region was seen as an essential source of community development and cultural preservation. The results of this study suggest implications for future studies on mediating effects of rurality in HE and recommendations for educational policy, specifically in the Least Developed Countries (LCDs) contexts concentrated in Sub-Saharan Africa (SSA).